2019
DOI: 10.1016/j.clinthera.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Serum Antibodies to Neuronal Proteins in Patients With Myalgic Encephalopathy/Chronic Fatigue Syndrome

Abstract: Purpose: A role for the immune system in causing myalgic encephalopathy/chronic fatigue syndrome (ME/CFS) is long suspected, but few studies have looked for specific autoantibodies that might contribute to the symptoms. Our aim was to look for evidence of antibodies to neuronal proteins in patients with ME/CSF.Methods: Sera samples from 50 patients and 50 healthy individuals were sent coded to the Neuroimmunology Laboratory in Oxford. Screening for antibody binding to neuronal tissue was performed on brain tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The increased GFAP levels in ME/CFS suggest a potential marker and pathobiology for that disorder. Recent studies from other groups have shown increased antibodies against ß2-adrenergic receptors in ME/CFS patients [ 50 , 51 ]. This suggests that ME/CFS is more similar to GWI than IBS based on these autoantibody biomarkers, but GWI still clearly represents a unique disorder based on different autoantibody patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The increased GFAP levels in ME/CFS suggest a potential marker and pathobiology for that disorder. Recent studies from other groups have shown increased antibodies against ß2-adrenergic receptors in ME/CFS patients [ 50 , 51 ]. This suggests that ME/CFS is more similar to GWI than IBS based on these autoantibody biomarkers, but GWI still clearly represents a unique disorder based on different autoantibody patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, some authors postulate that we could be facing an autoimmune pathology [ 79 ], at least in some of its forms, opening the possibility for a subgroup of patients (yet to be determined) to a treatment with immunomodulators or immunoadsorption [ 80 ]. However, recent publications did not find an increase in the frequency of autoantibodies, such as NMDA (related to some autoimmune encephalitis) nor LRP4, ACHR, and MuSK (associated with myasthenia gravis) [ 81 ], nor against the mitochondrial membrane [ 82 ]. Larger longitudinal studies are needed to determine the role of much of these antibodies, since they also appear elevated in control samples.…”
Section: Dysautonomiamentioning
confidence: 99%
“…In particular, a decrease in the adrenocorticotropic hormone sensitivity of adrenal cells and suppression of the negative feedback mechanism were detected [81]. Although some researchers did not find any differences between the levels of antineuronal AAb in CFS and healthy individuals [82], and others even found a decrease of AAb towards glial fibrillar acid protein in the sera of patients with CFS, which was correlated with exacerbations of the disease and the presence of Epstein‒Barr virus [83]. While both mast cells [84] and the innate immune system [85] were regarded as triggers for the focal inflammation in the hypothalamus in CFS, the role of the adaptive immune system should also be considered.…”
Section: Chronic Fatigue Syndrome and Fmmentioning
confidence: 99%